Investigating the phenomenon of overkill in Greece: A forensic psychiatric autopsy study between 2005 and 2020. (July 2021) - Karakasi, Maria-Valeria; Nastoulis, Evangelos; Zisopoulos, Konstantinos; Markopoulou, Maria; Alexandri, Maria; Bakirtzis, Christos; Douzenis, Athanassios; Zaggelidou, Eleni; Pavlidis, Pavlos
Abstract: The purpose of this study was to investigate overkill in the Greek population from a criminological and victimological point of view and explore possible correlations of the phenomenon with socio-cultural or psychiatric factors. Overall, 158 autopsies of overkill victims were identified throughout the 15-year records of the national forensic laboratories throughout the northern Greek mainland. The pattern that has emerged from the statistical results of the present study on the victims of overkill within the Greek borders was generally in line with global statistics on homicide victims, but also presented differences. The phenomenon correlated more with homicides in the context of mental disorders (within schizophrenia spectrum), other crimes (such as burglary) as well as domestic violence. Overall, males outnumbered females both as victims (approximately threefold) and as perpetrators in overkill homicide cases, but regarding domestic violence, the sad majority of overkill victims stood for females murdered with excessive violence by male relatives. Close female relatives (especially mothers and grandmothers) were also victimized by psychiatrically ill offenders. Female perpetrators tended to attack male individuals with whom they shared a relationship (intimate partners). An important finding was the fact that less than half the offenders' population with major mental disorders were diagnosed at the time of the offense. Overkill victims were found, on average, to be older than average homicide victims, being probably associated with the entailed difference in the physical strength ratio between the victim and the perpetrator. Highlights: Overkill criminological aspects are investigated via a 15-year autopsy study. Crimes correlated with schizophrenia spectrum disorders and domestic violence. Males were found to overall outnumber females both as victims and perpetrators. Females were victimized by male relatives in domestic/intrafamilial violence. Mothers and grandmothers were victimized by psychiatrically ill offenders.